Respostas

2014-08-07T12:20:34-03:00
  A=    0      3          B =      -2      4       C=     4      2         
          2      -5                     0      -1               -6      0      




A   +   B  =       0      3    +        -2      4            =        -2      7              
                        2    -5               0      -1                      2      -6


A + C =      0        3           +   4      2      =             4    5
                 2        -1               -6      0                     -4  -5


B  + C  + A    =    -2    4   +     4      2     +    0       3    =         2       9 
                           0    -1         -6      0           2      -5              -4      -6